Evaluation of a new cortical strip electrode for intraoperative somatosensory monitoring during perirolandic brain surgery. (October 2022) - Sarnthein, Johannes; Seidel, Kathleen; Neidert, Marian Christoph; Raabe, Andreas; Sala, Francesco; Tonn, Joerg Christian; Thon, Niklas; Szelenyi, Andrea
Highlights: We performed a prospective multicenter medical device study. Polymer strips with embedded metal nanoparticles had lower impedance than the comparator device. The electrodes achieved good signal-to-noise-ratio. Abstract: Objective: During neurosurgical procedures, strip electrodes should have low impedance and sufficient adherence on the brain surface. We evaluated the signal quality, safety, and performance of a novel strip electrode (WISE Cortical Strip, WCS®), with conductive electrode contacts created with platinum nanoparticles embedded in a polymer base. Methods: In a multicenter interventional, non-inferiority study, we compared WCS to a conventional strip electrode (Ad-Tech). We recorded impedance and somatosensory evoked potentials (SEP) and determined the signal-to-noise ratio (SNR). We performed direct stimulation of the motor cortex. An external clinical event committee rated safety and adverse events and users rated usability. Results: During 32 brain surgeries in the paracentral region, WCS was rated safe and effective in signal transmission. Two seizure events were classified as probably related to the stimulation with WCS. The users rated WCS adhesion to the brain as satisfactory but reported difficulties sliding the WCS under the dura. The median (IQR) impedance of WCS was lower than for Ad-Tech: 2.7 (2.3–3.7) vs 5.30 (4.3–6.6) kΩ ( p < 0.005). The SNR of SEP was non-inferior for WCS compared to Ad-Tech. Conclusions: The impedance of WCS was lower than Ad-Tech without safety limitations. In small craniotomies not exposing the motor cortex its use may be limited. Significance: Low impedance electrodes facilitate recordings with high SNR.